Influence of Cilnidipine on Catecholamine Release in the Perfused Rat Adrenal Medulla - Woo, Seong-Chang; Baek, Young-Joo; Lim, Dong-Yoon (The Korean journal of physiology & pharmacology, 2004)
The present study was attempted to investigate the effect of cilnidipine (FRC-8635), which is a newly synthesised novel dihydropyridine (DHP) type of organic $Ca^{2+}$ channel blockers, on secretion of catecholamines (CA) evoked by acetylcholine (ACh), high $K^+$, DMPP and McN-A-343 from the isolated perfused rat adrenal gland. Cilnidipine $(1{\sim}10μM)$ perfused into an adrenal vein for 60 min produced relatively dose- and time-dependent inhibition in CA secretory responses evoked by ACh $(5.32{×}10^{-3}M),\;DMPP\;(10^{-4}M\;for\;2\;min)$ and McN-A-343 $(10^{-4}M\;for\;2\;min)$. However, lower dose of cilnidipine did not affect CA secretion by high $K^+\;(5.6{×}10^{-2}\;M)$, higher dose of it reduced greatly CA secretion of high $K^{+}$. Cilnidipine itself did fail to affect basal catecholamine output. In the presence of cilnidipine $(10μM)$, the CA secretory responses evoked by Bay-K-8644 $(10μM)$, an activator of L-type $Ca^{2+}$ channels and cyclopiazonic acid $(10μM)$, an inhibitor of cytoplasmic $Ca^{2+}$-ATPase were also inhibited. Moreover, ${ω}-conotoxin\;GVIA\;(1μM)$, a selective blocker of the N-type $Ca^{2+}$ channels, given into the adrenal gland for 60 min, also inhibited time-dependently CA secretory responses evoked by Ach, high $K^+$, DMPP, McN-A-343, Bay-K-8644 and cyclopiazonic acid. Taken together, these results demostrate that cilnidipine inhibits CA secretion evoked by stimulation of cholinergic (both nicotinic and muscarinic) receptors from the isolated perfused rat adrenal gland without affecting the basal release. However, at lower dose, cilnidipine did not affect CA release by membrane depolarization while at larger dose inhibited that. It seems likely that this inhibitory effect of cilnidipine is exerted by blocking both L- and N-type voltage-dependent $Ca^{2+}$ channels (VDCCs) on the rat adrenomedullary chromaffin cells, which is relevant to inhibition of both the $Ca^{2+}$ influx into the adrenal chromaffin cells and intracellular $Ca^{2+}$ release from the cytoplasmic store. It is thought that N-type VDCCs may play an important role in regulation of CA release from the rat adrenal medulla.